PENGARUH MODEL PEMBELAJARAN PROBLEM POSING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VII SMP - Yahya, Ismail Saleh; Sanapiah, Sanapiah (Universitas Pendidikan Mandalika (UNDIKMA), 2016)
Problem posing an activity that emphasizes learning students to ask or create problems/questions and situations based on information provided by the teacher. The advantages of this learning, among others, to educate students to think critically, to make students actively participate in learning activities, it push students to analyze a problem, and educate students confidence. On the other hand, students of class VII SMPN 2 Selong still experiencing difficulties in understanding mathematical concepts, especially on the matter of integers. Under these conditions, the researchers want to conduct experiments to determine the effect of learning model problem posing on the ability of understanding mathematical concepts students of class VII SMPN 2 Selong. Experimental design used was quasi-experimental with posttes-only control group design. The sampling technique using cluster random sampling and set the class as a class experiment VII.1 and VII.2 class as the control class. Data regarding the ability of understanding the concept is taken using an instrument shaped test description. The results showed that through learning by problem posing models enable the pupils to achieve understanding of the concept which indicators to restate a concept, applying the concept or problem-solving, and classify objects according to certain properties in accordance with the concept